2018
DOI: 10.18632/oncotarget.24672
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of circulating microRNAs in upper tract urinary carcinoma

Abstract: The identification of upper tract urinary carcinoma (UTUC) prognostic biomarkers is urgently needed to predict tumour progression. This study aimed to identify serum microRNAs (miRNAs) that may be useful as minimally invasive predictive biomarkers of tumour progression and survival in UTUC patients. To this end, 33 UTUC patients who underwent radical nephroureterectomy at the Hospital Clinic of Barcelona were prospectively included. Expression of 800 miRNAs was evaluated in serum samples from these patients us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…In Annex B of the Additional file 1, we present a detailed analysis of the top 50 miRNAs in the signature, showing cancer study type, reference and circulating sample type used for measuring the expression. 23 miRNAs in the signature do not appear in the surveys, but they are mentioned in recent research papers, as promising research leads whose role may need further corroboration (we put the mature sequence as they appear in the study): miR-211 [54], miR-135a [55], miR-3678-3p [56], miR-204 [57], miR-1228 [58], miR-374b [59], miR-424 [60] miR-217-5p [60] miR-3613-5p [61], miR-124 [62], miR-1277-5p [63] miR-190 [64], miR-934 [65], miR-490 [66], miR-1247 [67], miR-199b [68], miR-135a [55], miR-503 [69], miR-584 [70], miR-137-3p [71], and miR-103 [72].…”
Section: Resultsmentioning
confidence: 99%
“…In Annex B of the Additional file 1, we present a detailed analysis of the top 50 miRNAs in the signature, showing cancer study type, reference and circulating sample type used for measuring the expression. 23 miRNAs in the signature do not appear in the surveys, but they are mentioned in recent research papers, as promising research leads whose role may need further corroboration (we put the mature sequence as they appear in the study): miR-211 [54], miR-135a [55], miR-3678-3p [56], miR-204 [57], miR-1228 [58], miR-374b [59], miR-424 [60] miR-217-5p [60] miR-3613-5p [61], miR-124 [62], miR-1277-5p [63] miR-190 [64], miR-934 [65], miR-490 [66], miR-1247 [67], miR-199b [68], miR-135a [55], miR-503 [69], miR-584 [70], miR-137-3p [71], and miR-103 [72].…”
Section: Resultsmentioning
confidence: 99%
“…The dysregulation of lipid metabolism, especially the abnormal elevation of LDL-C, is considered to be the main pathological basis of ASCVD [16]. At present, the circulating level of LDL-C is the most extensive diagnostic indicator for assessing and predicting the risk of atherosclerosis, and it has been globally acknowledged that reducing circulating LDL-C levels will effectively help in preventing ASCVD [14, 17]. Therefore, early intervention to inhibit circulating LDL-C levels has causally become more and more important.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, an increasing number of studies have shown that noncoding ribonucleic acids could be used for the early diagnosis of cardiovascular diseases and even play vital roles in the evaluation of therapeutic effects or prognosis [12, 13]. Wang GK et al demonstrated that plasma miR-208a might be a novel biomarker for acute myocardial infarction [14]. Fang Y et al found that miR-10a could regulate pro-inflammatory phenotypes in atherosclerosis-susceptible endothelium [15].…”
Section: Introductionmentioning
confidence: 99%
“…In 2014, a miRNA quality control (miRQC) study that evaluated 12 different technology platforms was published, which reported that the majority of platforms detected fewer than 90 miRNAs in human serum 19 . Since the miRQC study, newer platforms have emerged and reagent updates have been provided for several pre-existing platforms, but their relative performance in human biofluids is unclear 24 33 . Hence, an updated evaluation of miRNA quantitation platforms with a specific focus on human serum and plasma will be helpful.…”
Section: Introductionmentioning
confidence: 99%